PENINGKATAN KETERAMPILAN MENULIS DENGAN MODEL PEMÂ¬BELAJARAN COOPERATIF INTEGRATED READING AND COMPOSIÂ¬TION PADA SISWA KELAS IV SDN BACIRO, YOGYAKARTA TAHUN PELAJARAN 2015/2016 - Ajrina Khoirun Nisa; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2016)
This research aims to (1) an increase in the activity of the students in writing a narrative essay using model CIRC in class IV SDN Baciro Yogyakarta and (2) improving the skills of writing a narrative essay using model CIRC in class IV SDN Baciro Yogyakarta. This research is a classroom action research. Methods of data collection in this study using observation, tests, interviews, and documentation. The results showed that (1) CIRC learning methods can enhance the activity of fourth grade students of SDN Baciro. An examination of the enthusiastic students in pre cycle of 33.33%, 52.38% cycle 1 and cycle II 90.48%. Attention students at prasiklus 52.38%, 85.71% first cycle, the second cycle of 95.23%. Prasiklus student activity at 66.66%, 90.48% cycle 1, cycle II 90.48%. Pre-cycle student persistence at 14.28%, 42.85% cycle 1, cycle II 85.71% and (2) the use of the learning model can improve the CIRC narrative essay writing skills in grade IV SDN Baciro Yogyakarta. Judging from the contents of the ideas presented pre-cycle increase of 14.28%, 23.80% cycle 1, cycle II 61.90%. Aspects pre-cycle completeness of the content increased from 23.80%, 61.90% cycle 1, cycle II 90.47%. Pre-cycle grammar increase of 14.28%, 42.85% cycle 1, cycle II 80.95%. Style: the choice of structure and vocabulary of pre-cycle 33.33%, 52.38% cycle 1, cycle II 61.90%. Spelling and Grammar on prasiklus 33.33%, 57.14% cycle 1, cycle II 90.47%. The results above indicate that that the CIRC learning model can improve the activity and narrative essay writing skills in grade IV SDN Baciro.